DEVELOPING BILINGUAL SCIENTIFIC-WORKSHEET FOR INDEFINITE INTEGRAL - Laela Sagita; Rudha Widagsa; Nendra Mursetya Somasih Dwipa (Journal on Mathematics Education, 2018)
The purpose of this research was to develop a valid, practice and effective a bilingual scientific-worksheet of the indefinite integrals. This research is development research with 1) Preliminary investigation phase, 2) Prototyping phase, 3) Assessment phase. Data were collected from test and questionnaire and analyzed to examine validity, practicality, and effectiveness the worksheet. The result of this research was producing bilingual scientific-worksheet of indefinite integral materials that oriented for learning achievement improvement. The validity obtained content, language, and illustration from expert judgment. The practicality was on the relation, attention, belief, and student satisfaction. The effectiveness based on the result of achievement test on indefinite integral.